Dry Eye Disease after Cataract Surgery: Study of its Determinants and Risk Factors - Pragati Garg; Aditi Gupta; Nishi Tandon; Priyanka Raj (Türk Oftalmoloji Dergisi)

(untitled)
Objectives:To study the incidence of dry eye and its determinants in patients undergoing cataract surgery.Materials and Methods:One hundred twenty patients with senile cataract underwent Schirmer’s test, tear break-up time (TBUT) test, lissamine green staining of the cornea and conjunctiva, and Ocular Surface Disease Index (OSDI) for evaluation of dry eye preoperatively and again at first and second follow-up examinations at 1 week and 1 month after cataract surgery.Results:Mean age of the patients was 59.25+9.77 years and 73 (60.8%) were men. None of the patients had dry eye at the time of enrollment as per the criteria of our study. Postoperatively, Schirmer’s test values ranged from 12-35 mm and 8-24 mm at first and second follow-ups, respectively. Mean TBUT was 13.16±2.45 and 9.64±2.20 seconds, while lissamine green staining score was 3 in 67 (55.8%) and 1 in 67 (55.8%) subjects at first and second follow-up, respectively. OSDI values ranged from 1-30 and 10-33 with a mean of 25.97±5.34 and 11.96±7.47 respectively at first and second follow-up. At first follow-up, 89.1% of the 56 patients who underwent phacoemulsification were found to have grade 2 dry eye (p<0.001), while 92.2% of the 64 patients who underwent small-incision cataract surgery (SICS) had grade 2 dry eye (p<0.001). At second follow-up, grade 0 dry eye was observed in 92.2% of the patients who underwent phacoemulsification and 82.1% of the patients who underwent SICS (p<0.001).Conclusion:The incidence of dry eye after cataract surgery was high and mostly independent of demographic and anthropometric profile, type of surgical procedure, time of microscope exposure, and amount of energy used. This dryness was transient in nature and showed a declining trend, tending to achieve normalization by the end of 1 month.